Seismic damage evaluation of historical structures during Van earthquake, October 23, 2011. (December 2015) - Cakir, Ferit; Uckan, Eren; Shen, Jay; Seker, Burcin S.; Akbas, Bulent
Abstract: Seismic risk assessment of historical structures (mosques, churches, monuments, towers, palaces, aqua structures, etc.) has attracted many researchers' attention for the last few decades. This paper aims at investigating the damage at two historical structures, which partially collapsed during the main shock of the October 23, 2015, Van earthquake in eastern Turkey. The massive rigid body of both structures survived the earthquake without any damage, but the Narthexes of both structures collapsed. A thorough examination of the existing guidelines (ASCE 41, 2006; EC8-3, 2005 and PERPETUATE, 2010) are first studied. Response spectrum analyses are then performed to evaluate the seismic performance of the structures. The results of the numerical analyses revealed the fact that the collapse of the Narthexes could not be identified by the response spectrum analysis in which a sticked mode is assumed between both components. The failures of both structures were possibly due to local effects such as; independent responses of the Narthexes with respect to the main structure and/or weakened column-arch joints due to combined effects of environmental conditions and human interventions. Highlights: To investigate the evaluation procedures of historical slender masonry towers To examine the existing guidelines, such as ASCE 41, 2006; EC8-3, 2005 and PERPETUATE, 2010 To study the seismic performance and behavior of a historical slender masonry tower located in eastern Anatolia